PLURALITAS MAKNA DALAM “BEN GO TUN” KARYA SAINI K. M. MELALUI SEMIOTIKA BARTHESIAN - Lahpan, Neneng Yanti Khozanatu (Sunan Kalijaga State Islamic University Yogyakarta, 2022)
This article discusses one of Saini K.M’s drama plays entitled Ben Go Tun (1977), which was published in a book titled Five Witnesses (1999, 2000). The play is regarded as one of the best texts written by this senior playwright, which emphasizes on social problems and inequality in the setting of the New Order Era. Through literature studies and Barthesian's semiotic approach, this paper intends to explore various meanings in the text, in which a literary work is seen as a plural sign system. In its analysis processes, this approach follows a number of steps or procedures that include: 1) the division of the text into units of analysis (lexia), 2) the interpretation of lexias, and 3) a list of codes and their interpretations. Through hermeneutic, semic, symbolic, proairetic, and cultural codes, a number of interpretations are obtained, which illustrate that in the Ben Go Tun manuscript, there are some voices and perspectives in seeing the problems that arise in the story. The drama script is very dynamic in presenting the characters. It also presents various social criticisms with symbols that appear in diverse characters.